Prevalence of reactive hyperplastic lesions of the gingiva in the Western Indian population - Santosh R. Patil; Sneha Maheshwari; Suneet Khandelwal; Richa Wadhawan; Santosh Bankur Somashekar; Abhijeet Deoghare (Wolters Kluwer Medknow Publications, 2014)
Aim: The aim of the present study was to study the prevalence of reactive hyperplastic lesions of the gingiva in the western Indian population. Materials and Methods: A review of biopsy records of localized reactive hyperplastic lesions of the gingiva during the period from September 2007 to December 2013 was conducted from the Department of Oral and Maxillofacial Pathology. The lesions were studied according to the available clinical data regarding patient's age, sex, location, and size of the lesion. Results: The prevalence of reactive gingival lesions was 17.4%. The majority of the lesions were focal fibrous hyperplasia (FFH) (40.9%), followed by pyogenic granuloma (30%) with a female predominance. The lesions were commonly seen during the 2 nd and 3 rd decades of life. The lesions were equally distributed in both the jaws and the anterior region was the most commonly involved site. Conclusion: Focal reactive lesions are rather uncommon lesions of the oral cavity. The present study showed some difference in age and gender distribution, with FFH being the most common lesion in the north Indian population